2021
DOI: 10.1111/jog.14720
|View full text |Cite
|
Sign up to set email alerts
|

Pituitrin local injection versus uterine artery embolization in the management of cesarean scar pregnancy: A retrospective cohort study

Abstract: Aim To compare the effect of pituitrin local injection (PIT) and uterine artery embolization (UAE) as pretreatment before surgery during the management of cesarean scar pregnancy (CSP). Methods Forty‐nine CSP patients diagnosed in our department of Suzhou Ninth People's Hospital from October 2017 to October 2019. All patients underwent hysteroscopy and negative pressure aspiration (for type I CSP) or laparoscopic wedge‐resection (for type II and III CSP) following one of the preoperative treatments: PIT group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…UAE may be used alone or combined with local or systemic MTX for treatment of CSP. Moreover, it can be performed before uterine D&C, laparoscopy, hysteroscopy, or local resection [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…UAE may be used alone or combined with local or systemic MTX for treatment of CSP. Moreover, it can be performed before uterine D&C, laparoscopy, hysteroscopy, or local resection [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 19 ] reported that the value of prophylactic UAE during hysteroscopy in patients with type II CSP was uncertain. Wang et al [ 20 ] found that, compared with UAE pretreatment in the treatment of CSP, the pretreatment with local pituitrin injection appears to be the same: effective, more economical, and with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, over the past 10 years, the incidence of CSP has increased rapidly, owing to the increase in the number of cesarean sections being performed worldwide, and especially in mainland China, with the introduction of the two-child policy. 3 CSP can be categorized as type I (endogenic), characterized by growth toward the uterine cavity, and type II (exogenic), characterized by deep invasion of the uterine defect across the uterine serosa and toward the bladder and abdominal cavity. 4 If it is not diagnosed and treated early, type II CSP can result in uncontrollable hemorrhage, uterine rupture, damage to surrounding organs, and hysterectomy, which have negative effects on the reproductive health and lives of women.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, over the past 10 years, the incidence of CSP has increased rapidly, owing to the increase in the number of cesarean sections being performed worldwide, and especially in mainland China, with the introduction of the two-child policy. 3…”
Section: Introductionmentioning
confidence: 99%